Fabricate organic thermoelectric modules use modified PCBM and PEDOT：PSS materials - GAO, Feng; LIU, Yuchun; XIONG, Yan; WU, Ping; HU, Bin; XU, Ling (Frontiers of Optoelectronics (Online), 2017)
In this paper, we fabricated an organic thermo- electric （TE） device with modified [6,6]-phenyl-C61- butyric acid methyl ester （PCBM） and poly（3,4-ethylene- dioxythiophene） polystyrene sulfonate （PEDOT：PSS）; the device showed good stability in air condition. For n-leg, PCBM were doped with acridine orange base （3,6-bis （dimethylamino）acridine） （AOB） and 1,3-dimethyl-2,3- dihydro- 1H-benzoimidazole （N-DMBI）. Co-doped PCBM utilizes synergistic effects of AOB and N-DMBI, resulting in excellent electrical conductivity and Seebeck coefficient values reaching 2 S/cm and -500 μV/K, respectively, at room temperature with dopant molar ratio of 0.11. P-type leg used modified PEDOT：PSS. Based on modified PCBM and PEDOT：PSS materials, we fabricated a TE module device with 48 p-type and n-type thermocouple and tested their output voltage, short current, and power. Output voltage measured -0.82 V, and generated power reached almost 945 μW with 75 K temperature gradient at 453 K hot-side temperature. These promising results showed potential of modified PEDOT and PCBM as TE materials for application in device optimization.